International Commission for the History and Theory of Historiography Book Prize 2016 - Lorenz, Chris FG (Historein, 2015)
Applications are now open for the International Commission for the History and Theory of Historiography (ICHTH) International Book Prize and the ICHTH Doctoral Dissertation Prize for the History and Theory of Historiography. Worth 500 each, the prizes are offered alternately for the best doctoral dissertation and book on any aspect of the history and the theory of historiography.